2019
DOI: 10.5530/pj.2019.11.37
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Phytochemical, Vitamins Composition and Antioxidant Activity of Pelargonium inquinans Leaves

Abstract: Aims: To estimate the phytochemical and vitamins composition and the antioxidant activity of Pelargonium inquinans leaves. Background: Some plants that are used in the traditional setting for the management of different ailments have documented observations and scientific studies. However many other plants lack scientific reports to support their medicinal use. One of such plant is Pelargonium inquinans Ait that is traditionally used to treat headaches and flu by tribes in South Africa. Not much is known about… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…The total tannin content was estimated according to the method described previously (Izuegbuna et al., 2019). A 100 μL of extract/fraction, 7.5 mL of deionised water, 500 μL of 10% (v/v) Folin–Ciocalteu reagent and 1 mL of 35% Na 2 CO 3 solution were all added to a tube and well mixed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The total tannin content was estimated according to the method described previously (Izuegbuna et al., 2019). A 100 μL of extract/fraction, 7.5 mL of deionised water, 500 μL of 10% (v/v) Folin–Ciocalteu reagent and 1 mL of 35% Na 2 CO 3 solution were all added to a tube and well mixed.…”
Section: Methodsmentioning
confidence: 99%
“…Estimation of total flavonoid content The total flavonoid content was estimated according to the method described previously (Izuegbuna et al, 2019). A 500 μL of the extract (or fraction) was placed in a tube and mixed with 300 μL of 5% sodium nitrite.…”
Section: Evaluation Of Phytochemical Activitymentioning
confidence: 99%
“…A search of the literature did not reveal any information about the hydrogen peroxide scavenging capacity of HRLs of P. sidoides. According to previous results, Izuegbuna et al 44 showed the scavenging ability of P. inquinans leaves was high and dose-dependent, which could be a result of high levels of phenolic compounds and avonoids with high amounts of polyphenol, and antioxidant activities 45 . The overall results…”
Section: Discussionmentioning
confidence: 92%
“…The free radical scavenging ability of the leaf extracts against 2,2-diphenyl-1-picrylhydrazyl (DPPH) was evaluated according to the procedure described by Izuegbuna et al [19] with a slight modification. Ascorbic acid solution (0.2-1.0 mg/mL) was taken as the standard.…”
Section: Dpph Radical Scavenging Assaymentioning
confidence: 99%